Global maps of the step-wise topography corrected and crustal components stripped geoids using the CRUST 2.0 model - TENZER, Robert (Contributions to Geophysics and Geodesy, 2009)
We compile global maps of the step-wise topography corrected and crustal components stripped geoids based on the geopotential model EGM’08 complete to spheri- cal harmonic degree 180 and the CRUST 2.0 global crustal model. The spectral resolution complete to degree 180 is used to compute the primary indirect bathymetric stripping and topographic eﬀects on the geoid, while degree 90 for the primary indirect ice stripping eﬀect. The primary indirect stripping eﬀects of the soft and hard sediments, and the upper, middle and lower consolidated crust components are forward modeled in spatial form using the 2 × 2 arc-deg discrete data of the CRUST 2.0 model. The ocean, ice, sediment and consolidated crust density contrasts are deﬁned relative to the adopted ref- erence crustal density of 2670 kg/m3 . Finally we compute and apply the primary indirect stripping eﬀect of the density contrast (relative to the mantle) of the reference crust. The constant value of −520 kg/m3 is adopted for this density contrast relative to the mantle. All data are evaluated on a 1 × 1 arc-deg geographical grid. The complete crust-stripped geoidal undulations, globally having a range of approximately 1.5 km, contain the gravi- tational signal coming from the global mantle lithosphere (upper mantle) morphology and density composition, and from the sub-lithospheric density heterogeneities. Large errors in the complete crust-stripped geoid are expected due to uncertainties of the CRUST 2.0 model, i.e., due to deviations of the CRUST 2.0 model density from the real earth’s crustal density and due to the Moho-boundary uncertainties.